2021
DOI: 10.1021/acsbiomaterials.1c00232
|View full text |Cite
|
Sign up to set email alerts
|

Inducing Immunomodulatory Effects on Human Macrophages by Multifunctional NCO-sP(EO-stat-PO)/Gelatin Hydrogel Nanofibers

Abstract: Endowing materials and scaffolds with immunomodulatory properties has evolved into a very active field of research. However, combining such effects with multifunctionality regarding cell adhesion and manipulation is still challenging due to the intricate nature of cell–substrate interactions that require fine-tuning of scaffold properties. Here, we reported electrospinning of a well-known biopolymer, gelatin, together with six-arm star-shaped poly­(ethylene oxide-stat-propylene oxide) prepolymer with isocyanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…The change of macrophage phenotype is related to matrix stiffness. On the surface of the high stiffness matrix, macrophages are pro-inflammatory phenotype, while on the surface of low stiffness matrix, macrophages are anti-inflammatory phenotype ( Trel’ová et al, 2019 ; Taskin et al, 2021 ). Changes in macrophage phenotypes, in turn, alter the expression of related cytokines, which can affect the bone microenvironment ( YlÖstalo et al, 2012 ; Liu et al, 2018 ; Esser-von Bieren, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The change of macrophage phenotype is related to matrix stiffness. On the surface of the high stiffness matrix, macrophages are pro-inflammatory phenotype, while on the surface of low stiffness matrix, macrophages are anti-inflammatory phenotype ( Trel’ová et al, 2019 ; Taskin et al, 2021 ). Changes in macrophage phenotypes, in turn, alter the expression of related cytokines, which can affect the bone microenvironment ( YlÖstalo et al, 2012 ; Liu et al, 2018 ; Esser-von Bieren, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Doryab et al developed a hybrid biphasic membrane (composed of gelatin and PCL) for an in vitro cell stretch model of the lung cultured under ALI conditions [45]. Taskin et al electrospun various ratios of six-arm star-shaped poly (ethylene oxide-propylene oxide) prepolymers with isocyanate end groups (NCO-sP [EO-stat-PO]) to stabilize gelatin as a bioactive component within nanofibrous hydrogel scaffolds [46]. Zamprogno et al used biofilms made of lung ECM, collagen and elastin proteins for stretch culture [39].…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Drug Delivery frontiersin.org was suggested that the honeycomb-like texture can promote filopodia formation, which is associated with RhoA/ROCK signaling pathways, and can induce M2 polarization (Zhu et al, 2021). Moreover, a study reported that fibrous meshes of gelatin hydrogel nanofibers mimicking ECM promoted macrophage adhesion and differentiation into M2 phenotypes, with upregulation of CD206 expression and downregulation of IL-1β and IL-8 in in vitro culture (Taskin et al, 2021).…”
Section: Surface Topography and Porositymentioning
confidence: 99%